Apply the Search Engine Optimization (SEO) Method to determine Website Ranking on Search Engines - Fifin Alfiana; Nimatul Khofifah; Tarisya Ramadhan; Nanda Septiani; Wahyuningsih Wahyuningsih; Nadia Nur Azizah; Nova Ramadhona (International Institute for Advanced Science & Technology (IIAST), 2023)
In today's digital age, the internet has become an essential tool for various activities, including business promotion. One effective way to promote your business online is by creating a website that offers useful information to visitors. However, simply having a website is not enough; it is crucial to ensure that your website ranks high on search engine results pages (SERPs) in order to attract more visitors. One of the most effective methods to optimize a website for search engines is through search engine optimization (SEO) techniques. These techniques aim to improve a website's visibility on SERPs by using various tactics, such as keyword research, content optimization, and link building. However, it is important to note that SEO optimization is not a one-time task but rather an ongoing process. It requires constant attention and effort to maintain high search engine rankings and ensure the continued success of your online business. By optimizing your website, you can improve its visibility on search engines, attract more visitors, and ultimately drive business growth. It is important to remain vigilant in implementing SEO techniques to maintain high search engine rankings and ensure the continued success of your online business.